The Impact of Earnings Quality on the Probability of Bankruptcy in Companies Listed on the Iraq Stock Exchange: An Instrumental Variables Approach - Majeed Mozan Al-Saedi, Dunya; Fooladi, Masood; Farhan, Mezban Mohammed; Sharifi, Saeid; Farhadi, Maryam (Business, Marketing, and Finance Open, 2025)
A company faces the risk of financial distress when it is unable to secure sufficient financial resources to sustain its business operations and encounters difficulties in managing its affairs. Decision usefulness theory suggests that high earnings quality is considerably more beneficial for investment decisions, whereas low earnings quality is less effective in the decision-making process. Consequently, high earnings quality reflects earnings sustainability, which, based on signaling theory, indicates signs of operational health and fewer threats to the company’s future viability. Given that previous studies on the relationship between earnings quality and the probability of bankruptcy have not addressed the endogeneity issue of earnings quality, the present study aims to investigate the effect of earnings quality on the probability of bankruptcy using an instrumental variables approach and applying the two-stage least squares (2SLS) estimator. The study population includes all companies listed on the Iraq Stock Exchange from 2013 to 2022. The findings reveal that an increase in earnings quality reduces the probability of bankruptcy among companies listed on the Iraq Stock Exchange.